Chiral Templating of Polycarbonate Membranes by Pinene Using the Modified Atomic Layer Deposition Approach - Brozova, Libuse; Zazpe, Raul; Otmar, Miroslav; Přikryl, Jan; Bulánek, Roman; Zitka, Jan; Krejcikova, Sabina; Izak, Pavel; Macák, Jan (American Chemical Society, 2020)
In this article, chiral templating of a polycarbonate (PC) membrane by (-)-alpha-pinene using the atomic layer deposition (ALD) approach is investigated. The templating with the enantiomer of (-)-alpha-pinene, used as a case compound, was performed either on the original commercial PC membrane or on the PC membrane with a beforehand deposited Al2O3 layer. The efficiency of the templating was assessed by a difference in the membrane ability to adsorb/absorb (-)-alpha-pinene, (+)-alpha-pinene, and their racemic mixture, using a very sensitive gas sorption analyzer. The results clearly show that the solution-diffusion mechanism rather than the sieving mechanism applied for adsorption/absorption of (-/+)-alpha-pinene enantiomers, which have the same size of the molecule. The PC membrane with the predeposited Al2O3 before the (-)-alpha-pinene templating shows significantly higher sorption of (-)-alpha-pinene compared to (+)-alpha-pinene and racemate, which clearly demonstrates the presence of a chiral recognition effect.
Chirální templátování polykarbonátových membrán pinenem pomocí modifikovaného přistupu depozice atomárních vrstev
Keywords: liquid-chromatography; polymeric membranes; nafion(r) membranes; enantiomers; separation; hysteresis; sorption; enantioseparation; pharmaceuticals; desorption; chirální templátování; polykarbonát; trimetylaluminum; enantiomer; pinen